2015
DOI: 10.1515/ami-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged stopover duration characterises migration strategy and constraints of a long-distance migrant songbird

Abstract: Stopover behaviour is a central element of migration strategies. But in recent geolocator studies, despite now being able to track individual songbirds during their entire migration, their stopover behaviour has received little attention. We used light-sensitive geolocators to identify the migratory routes and schedules of 12 northern wheatears (Oenanthe oenanthe) breeding in Sweden. Three geolocators collected temperature data complementing inferences from light data by providing additional information on beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 9 publications
6
51
0
Order By: Relevance
“…We defined arrival date as the date when an individual was first observed in the study area (relative to 1st May). Those observed arrival dates closely corresponded to arrival dates estimated from geolocation data from a smaller sample of birds ( N = 12, median difference of 2 days [range 0–4]; Arlt, Olsson, Fox, Low, & Pärt, ). We collected arrival and breeding data during 20 years (1993–1996 and 2002–2017 [arrival data were not routinely collected from 1997–2001]) and only included data from areas where territories were frequently visited (every 2–3 days) during the arrival period, from early April to 10th May.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…We defined arrival date as the date when an individual was first observed in the study area (relative to 1st May). Those observed arrival dates closely corresponded to arrival dates estimated from geolocation data from a smaller sample of birds ( N = 12, median difference of 2 days [range 0–4]; Arlt, Olsson, Fox, Low, & Pärt, ). We collected arrival and breeding data during 20 years (1993–1996 and 2002–2017 [arrival data were not routinely collected from 1997–2001]) and only included data from areas where territories were frequently visited (every 2–3 days) during the arrival period, from early April to 10th May.…”
Section: Methodssupporting
confidence: 72%
“…We defined arrival date as the date when an individual was first observed in the study area (relative to 1st May). Those observed arrival dates closely corresponded to arrival dates estimated from geolocation data from a smaller sample of birds (N = 12, median difference of 2 days [range 0-4]; Arlt, Olsson, Fox, Low, & Pärt, 2015).…”
Section: The Wheatear Study Systemsupporting
confidence: 73%
“…There is evidence that total speed of migration increases with population‐specific total migration distance (Arlt, Olsson, Fox, Low, & Pärt, ; Bairlein et al., ; Schmaljohann, Buchmann, Fox, & Bairlein, ; Schmaljohann, Fox, & Bairlein, ). To increase total speed of migration, birds may decrease their total stopover duration (Schmaljohann & Both, ) and/or increase their travel speed.…”
Section: Introductionmentioning
confidence: 99%
“…The stopover sites found in north Africa are at the same latitude as Crete, and since the desert more or less reaches the Mediterranean in the east, stopover in southern Greece might be a strategy for great reed warblers following a more eastern route. Recent geolocator studies have also shown longer stopover periods in northwest Africa following the Sahara crossing in turtle doves Streptopelia turtur and northern wheatears Oenanthe oenanthe (Eraud et al , Arlt et al ). The stopover periods found in northern wheatears were on average 18.5 d, which the authors believe is longer than needed for refuelling, and they suggest that it might partly be a strategy of using areas with good foraging conditions at a time when conditions in the wintering areas have deteriorated (Arlt et al ).…”
Section: Discussionmentioning
confidence: 99%